Qualidade do café natural especial acondicionado em embalagens impermeáveis e armazenado no Brasil e no exterior - Andrade, Fabrício Teixeira (2017)
Edaphoclimatic conditions, technological level of coffee culture and the volume of Natural coffee produced in Brazil grants the country great potential for producing natural specialty coffees. However, to consistently meet the many markets, it is necessary to conserve the quality of coffee grain for long periods, comparable to the needs of the agents present along the production chain. For this, adequate storage conditions are necessary, given that the climbing quality reduction is conditioned especially by factors such as initial water content of the product, environmental storage conditions and the intergranular atmospheric composition within the package, especially concerning oxygen and carbon dioxide. Thus, it is important to develop new technologies for packaging the crude grain that meet the needs of the specialty coffee market. In this context, the objectives of this work were: i) evaluate the quality of crude grains of natural specialty coffees packaged in different packages over storage in Brazil, and ii) evaluate the behavior of crude grains of natural specialty coffees packaged in different packages since storage in Brazil, going through sea transportation under commercial conditions, to the final destination, with subsequent storage in importing company of specialty coffees. One lot of crude grains of natural specialty coffees from the 2014 harvest, were provided by coffee export companies. The coffee grains were initially homogenized, packaged in eight types of packaging and stored in commercial storage located in Poços de Caldas, Minas Gerais, Brazil. The first experiment was conducted in a 8x6 factorial scheme, corresponding to eight packaging methods and six storage periods (0, 3, 6, 9, 12 and 18 moths). The second experiment was conducted in 8x4 factorial scheme, corresponding to eight packaging methods and four storage periods (0, 3, 6 and 12 months). Until three months, the packages containing the crude coffee grains remained in Brazil, under commercial conditions, and, after three months, the packages were exported to the United States, where they were stored for 14 months. In conclusion, the packaging with high barrier were recommended for storage and exportation of crude specialty coffee grains for long periods for providing better grain conservation when compared to the protection offered by packages with or without low barrier to gasses and moisture.